STABILITY AND SUNSCREEN ACTIVITY OF NUTMEG SEED OIL EMULGEL WITH CARBOPOL 940 VARIATION AS GEL BASE - Ilma Nur Khafifa; Ayu Shabrina; M Fatchur Rochman (Jurnal Farmasi Sains dan Praktis, 2022)
The nutmeg seed oil has antioxidant and sunscreen activity, but it is unstable in storage. The stability of nutmeg seed oil can be improved by developing the oil into an emulgel with carbopol 940. This study determined the stability of nutmeg seed oil emulgel (NSE) with carbopol 940 as a gel base. NSE contains of 10% nutmeg oil and variation of carbopol 940 were 0.60% (FI), 0.80% (FII), and 1.0% (FIII). NSE was tested for SPF value every week and physical stability, including organoleptic, homogeneity, adhesion, dispersibility, viscosity, and pH before and after 30 days of storage. NSE was stored at the climatic chamber at 30±2°C with RH 65±5%. Quantitative data from physical stability were analyzed by t-test dependent while SPF value and antioxidant were analyzed by univariate test. All the physical parameters showed no significant changes (p > 0.05). Emulgel was white thick, with a nutmeg seed oil odor. pH was in a safe range for skin (6.12-6.90). NSE had pseudo-plastic rheology, and it changed into pseudoplastic-thixotropic after 30 days of storage. The SPF value of NSE was above eight, and it did not show significant change after the storage from each week (p > 0.05). Nutmeg seed oil emulgel with carbopol 940 showed stable physical appearance and SPF value.